Konsep Mahabbah dalam Al-Qur’an - Zuherni Zuherni; Raudhatul Jannah Ilyas (TAFSE: Journal of Qur'anic Studies, 2018)
Human love is nature from God. Mahabbah or love for fellow human beings in the form of love for parents, children, husband and wife and relatives is something that is natural, because of closeness and other emotional relationships. Moreover, love for them is based on love for Allah swt. However, all of this is forbidden if love for those closest to him turns him away from Allah, making him close his eyes in distinguishing between right and wrong. On the basis of this thought, it is necessary to study how to place the love of fellow human beings in accordance with the instructions of the Qur'an. The results of this paper indicate that love for fellow human beings both for parents, children, husband and wife and relatives in Islam is highly recommended, but if this love makes someone associate partners with Allah, commit immorality and disobey the Messenger of Allah, then love for fellow humans is not justified. Rasa cinta yang dimiliki manusia merupakan suatu fitrah dari Allah. Maḥabbah atau cinta sesama manusia berupa cinta kepada orang tua, anak, suami istri dan sanak saudara sesuatu yang alami, karena kedekatan dan hubungan emosional lainnya. Apalagi cinta kepada mereka didasari pada cinta kepada Allah swt. Akan tetapi, semua itu dilarang jika dengan cinta kepada orang-orang terdekat membuatnya berpaling dari Allah, membuat mata dia tertutup dalam membedakan antara yang benar dan yang salah. Atas dasar pemikiran inilah perlu dikaji bagaimana menempatkan cinta sesama manusia yang sesuai dengan petunjuk al-Qur’an. Hasil penulisan ini menunjukkan bahwa cinta sesama manusia baik kepada orang tua, anak, suami istri maupun sanak saudara di dalam Islam sangat dianjurkan, namun apabila cinta ini membuat seseorang menyekutukan Alah, berbuat maksiat serta ingkar kepada Rasulullah, maka rasa cinta kepada sesama manusia tidak dibenarkan.